Dialysate Flow: Is the Less the Better? (2020)
Minimization of Qd is a matter of interest for our group not only in terms of dialysis efficiency and patient safety but also in terms of reduction of wastage in water. Since 2012, we have been prescribing Qd 400 mL/min for small patients, and we have already shared our experience [1, 2].We found no differences in Kt/V, phosphate, hemoglobin, potassium, and interdialytic gain between our Qd groups Table 1 [3]. Recently we have successfully finished our 5-year analysis of mortality between Qd 400 and 500 mL/min in a chronic HD population in Colombia. Our results were shared in the ISN Congress next April in Melbourne in the poster session on the topic green nephrology as one of our Blue Planet dialysis initiative